J. Y. Pillay [Singapore, Civil Service] - Pillay, Joseph Yuvaraj (Institutional Knowledge at Singapore Management University, 2015)
In this DNA interview, Chancellor of Singapore Management University and former top Singapore civil servant, J.Y. Pillay, tells of qualities of good leaders, and the leadership styles of his former bosses Hon Sui Sen and Goh Keng Swee. Known for being a leader who listens and focuses well, he reveals his process of making controversial decisions in the past.